Impact of rare yeasts in Saccharomyces cerevisiae wine fermentation performance: Population prevalence and growth phenotype of Cyberlindnera fabianii, Kazachstania unispora, and Naganishia globosa. (April 2023) - Vicente, Javier; Ruiz, Javier; Tomasi, Sandra; de Celis, Miguel; Ruiz-de-Villa, Candela; Gombau, Jordi; Rozès, Nicolás; Zamora, Fernando; Santos, Antonio; Marquina, Domingo; Belda, Ignacio
Abstract: Saccharomyces cerevisiae is a highly fermentative species able to complete the wine fermentation. However, the interaction with other non- Saccharomyces yeasts can determine the fermentation performance of S. cerevisiae . We have characterised three rare non- Saccharomyces yeasts ( Cyberlindnera fabianii, Kazachstania unispora and Naganishia globosa ), studying their impact on S. cerevisiae fitness and wine fermentation performance. Using a wide meta-taxonomic dataset of wine samples, analysed through ITS amplicon sequencing, we show that about a 65.07% of wine samples contains Naganishia spp., a 27.21% contains Kazachstania spp., and only a 4.41% contains Cyberlindnera spp; in all cases with average relative abundances lower than 1% of total fungal populations. Although the studied N. globosa strain showed a limited growth capacity in wine, both K. unispora and C. fabianii showed a similar growth phenotype to that of S. cerevisiae in different fermentation conditions, highlighting the outstanding growth rate values of K. unispora . In mixed fermentations with S. cerevisiae, the three yeast species affected co-culture growth parameters and wine chemical profile (volatile compounds, polysaccharides and proteins). K. unispora DN201 strain presents an outstanding capacity to compete with S. cerevisiae strains during the first stage of wine fermentation, causing stuck fermentations in both synthetic and natural grape musts. Highlights: The prevalence of Cyberlindnera spp. in wine populations is about 4% of samples. The prevalence of Kazachstania spp. in wine populations is about 27% of samples. The prevalence of Naganishia spp. in wine populations is about 65% of samples. Kazachstania unispora DN201 caused stuck fermentations. K.unispora DN201 has high nitrogen consumption rate and production of acetic acid.